The assessment of body representation in adults through computer-based tasks - Raimo, Simona; Gaita, Mariachiara; Malangone, Daniela; Dolce, Erica; Ammendola, Lidia; Canino, Silvia; Torchia, Valentina; Panzino, Giada; Aquino, Mariamichela; Cropano, Maria; Di Vita, Antonella; Boccia, Maddalena; et al. (Frontiers in Psychology, 2025)
IntroductionThis study aims to evaluate the use of computer-based body representation tasks in an adult sample, considering the role of demographic variables and providing correction indices for clinical practice.MethodThree hundred sixty-six healthy participants were assessed in person with a computer-based battery that included the Hand Laterality Task (HLT) to assess action-oriented body representation (aBR), the Frontal Body Evocation Task (FBET) to assess nonaction-oriented body representation (NaBR), and two corresponding control tasks (i.e., the Object Laterality Task and the Christmas Tree Task), to disentangle the effect of cognitive functions required to perform the tasks but independent of body representation processing. In addition to the primary cohort, 305 healthy participants performed similar body representation and control tasks in an unsupervised web-based version, and a subgroup of these (N = 30) underwent the assessment in both the laboratory-based and web-based versions.ResultsConcerning the body representation tasks, multiple linear regression analysis revealed that age and sex significantly influenced aBR accuracy and response time (i.e., the HLT), while the NaBR accuracy and response time (i.e., the FBET) were significantly influenced only by age. A correction grid was constructed from the derived linear equation to adjust raw scores according to demographic variables, and a percentile distribution of adjusted scores was provided for each task. Correlation analyses showed significant and strong correlations between the laboratory-based and web-based versions of the tasks (r ≤ 0.888; ps < 0.001), supporting the use of these tasks for the remote assessment.DiscussionThe provided normative data can be helpful for clinical and research purposes, and we discuss the potential benefits of their use.